2018
DOI: 10.1177/0004865817748179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indigenous status on sentence outcomes for serious assault offences

Abstract: Recent studies have found evidence of a racial bias in sentencing in Australia despite previous work showing the opposite. However, in some cases, these studies fail to adjust properly for differences in offence seriousness and in others fail to control for important covariates. Our aim in this study was to investigate the relationship between Indigenous status and likelihood of imprisonment for serious assault offences, matching on offence seriousness and controlling for additional covariates. Multivariate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The study had several limitations that could be addressed in future research. First, although Thorburn and Weatherburn (2018) have observed that offense history and seriousness account for disparity in Indigenous and non-Indigenous sentencing outcomes in Australia, they also note that this appears not to be the case when the principal offense is domestic violence related. In this case, differences in sentencing outcomes are observable even after adjusting for offense history and seriousness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study had several limitations that could be addressed in future research. First, although Thorburn and Weatherburn (2018) have observed that offense history and seriousness account for disparity in Indigenous and non-Indigenous sentencing outcomes in Australia, they also note that this appears not to be the case when the principal offense is domestic violence related. In this case, differences in sentencing outcomes are observable even after adjusting for offense history and seriousness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific contribution of sentencing to Indigenous overrepresentation is less clear. Australian research is somewhat divided on whether Indigenous people are more likely to be sentenced to a term of imprisonment even after controlling for criminal history and offense seriousness variables (Fitzgerald, 2009; Jeffries & Bond, 2012; Thorburn & Weatherburn, 2018). Yet, recent research suggests sentencing disparity may be less ambiguous in relation to domestic violence.…”
mentioning
confidence: 99%
See 3 more Smart Citations